The Influence of Cause-Related Marketing on Millennials’ Purchase Intentions: Evidence of CSR from an Emerging Economy - Swapna J Shetty; Molly Sanjay Chaudhuri; Ankitha Shetty (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2021)
Corporate social responsibility (CSR) has been implemented through sponsorships, philanthropy, and cause-related marketing (CRM), amongst which CRM has aroused the interest of many academicians and stakeholders. The study aims to examine the antecedents of cause-related marketing while considering attitude as a mediator to test its relationship with the purchase intention. The snowball sampling technique for data collection was administered to Indian millennial consumers from the regions of Karnataka and Kerala. A total of 313 valid cases were selected for the analysis, which employed partial least squares (PLS) based on structural equation modeling (SEM). The findings have shown that a positive relationship exists between cause participation and purchase intention. Further, product/cause congruence & consumer/cause identification had a positive impact on attitude, while attitude, in turn, showed a favorable association with the purchase intention. This study disclosed the relative importance of the compatibility between the social causes supported by the company with its engaged business while adopting CRM campaigns, and highlighted the need for the involvement of consumers in the CRM programs for their effectiveness.